Proteomic peptide phage display uncovers novel interactions of the PDZ1‐2 supramodule of syntenin. Issue 1 (8th January 2016) - Garrido‐Urbani, Sarah; Garg, Pankaj; Ghossoub, Rania; Arnold, Roland; Lembo, Frédérique; Sundell, Gustav N.; Kim, Philip M.; Lopez, Marc; Zimmermann, Pascale; Sidhu, Sachdev S.; Ivarsson, Ylva
Abstract : Syntenin has crucial roles in cell adhesion, cell migration and synaptic transmission. Its closely linked postsynaptic density‐95, discs large 1, zonula occludens‐1 (PDZ) domains typically interact with C‐terminal ligands. We profile syntenin PDZ1‐2 through proteomic peptide phage display (ProP‐PD) using a library that displays C‐terminal regions of the human proteome. The protein recognizes a broad range of peptides, with a preference for hydrophobic motifs and has a tendency to recognize cryptic internal ligands. We validate the interaction with nectin‐1 through orthogonal assays. The study demonstrates the power of ProP‐PD as a complementary approach to uncover interactions of potential biological relevance. Abstract :